Penggalian Kurikulum Pendidikan Agama Islam Melalui Pengembangan Kemampuan Mahasiswa Di Era Pandemic Covid 19 Menuju Era New Normal - Asfiati Asfiati (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
The Covid 19 Pandemic era and the new normal era had a number of regulations. The period of the Covid 19 pandemic, which has a cautious attitude, is the basis for developing a number of abilities.The abilities that are intended are those that can be explored in developing the Islamic Religious Education curriculum. The ability of students must be adjusted to the conditions of learning and development needs as one of the pathways for achieving the goals of the curriculum.Learning Islamic Religious Education during the Covid 19 and New Normal pandemic tends to be virtual by developing digital student abilities. The period of the Covid 19 pandemic and the new normal era was a period where the ability of students to have various assets sourced from the internet and Google were initiated by teachers and lecturers to be developed, guided and analyzed.Teachers and Lecturers are responsible for guiding, analyzing and assessing the abilities of students which are the basic sources of extracting the Islamic Religious Education curriculum. Teachers and Lecturers continue to adapt it to the scope of Islamic Religious Education. The existence of students in the Covid 19 pandemic era towards the new normal era with academic protocol programs was carried out carefully. Productive students are safe covid. Students who are sent to the new normal era.The Covid 19 Pandemic era and the new normal era had a number of regulations. The period of the Covid 19 pandemic, which has a cautious attitude, is the basis for developing a number of abilities.The abilities that are intended are those that can be explored in developing the Islamic Religious Education curriculum. The ability of students must be adjusted to the conditions of learning and development needs as one of the pathways for achieving the goals of the curriculum.Learning Islamic Religious Education during the Covid 19 and New Normal pandemic tends to be virtual by developing digital student abilities. The period of the Covid 19 pandemic and the new normal era was a period where the ability of students to have various assets sourced from the internet and Google were initiated by teachers and lecturers to be developed, guided and analyzed.Teachers and Lecturers are responsible for guiding, analyzing and assessing the abilities of students which are the basic sources of extracting the Islamic Religious Education curriculum. Teachers and Lecturers continue to adapt it to the scope of Islamic Religious Education. The existence of students in the Covid 19 pandemic era towards the new normal era with academic protocol programs was carried out carefully. Productive students are safe covid. Students who are sent to the new normal era.